Analisa Peralihan Tanggapan Tegangan Sistem Automatic Voltage Regulator (AVR) Tipe Arus Searah Dengan Pengendali 2 Derjat Kebebasan - Laksono, Heru Dibyo (JURNAL AMPLIFIER : JURNAL ILMIAH BIDANG TEKNIK ELEKTRO DAN KOMPUTER, 2021)
This journal discusses the design and analysis of the transfer response of the direct cuurent type of Automatic Voltage Regulator (AVR) system with 2 degrees of freedom controller. Direct current type of the AVR system is represented in the form of transfer function. For 2 degrees of freedom controllers are designed using a parallel architecture with the help of Matlab software using predefined design criteria. The types of controllers used consist of Proportional Differential (PD), Proportional Integral (PI), Proportional Integral Differential (PID), Proportional Differential with First Order Filters in the Differential Section (PDF) and Proportional Intregral Differential with First Order Filters in the Differential Section (PIDF). For the transition analysis, the observed parameters consist of rise time, peak time, steady state time, maximum pass value and peak value. The results of the analysis show that the controller that meets the design criteria is a Proportional Differential (PD) controller with an uptime parameter value of 0.2808 seconds, a peak time of 1.3354 seconds, a steady state time of 0.7017 seconds, a maximum pass of 0% and a peak value of 0.9512. For the Proportional Differential controller with First Order Filter in the Differential Section (PDF) with an increase time parameter value of 0.4177 seconds, a peak time of 1.4684 seconds, a steady state time of 0.8453 seconds, a maximum pass of 0% and a peak value of 0.9502.